EFFECT OF BACTERIAL BIOFERTILIZER AND COMPOST ON THE GROWTH OF TOMATO PLANT - & Al-Whaab, Salman (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2016)
A pot experiment was conducted at Baghdad site for organic fertilizer preparation Plant Protection Directorate during summer of 2014-2015, using sandy Loam texture soil to study the effect of bacterial bio-fertilizer ( Azotobacter chroococcum and Pseudomonas fluorescens ) and Compost on growth and nutrients content of tomato plants "Super queen". Eight treatments were used included (Control , Azotobacter , pseudomonas, Azotobacter+ psuedomonas , Compost , Azotobacter + Compost , Compost+ psuedomonas , Azotobacter + psuedomonas + Compost). Complete Randomized Design ( CRD ) with 5 replicates was used. Results showed that application of di bacterial bio-fertilizer (AP) increased significantly dry mater weight and N , P , K nutrients content for shoots with an increment of 36.4%,74.4%,76.0% and 64.9% respectively compared to control. Results showed that application of di bacterial bio-fertilizer (AP) and compost increased significantly dry matter weight and N , P , K nutrients content for shoot with increment percentage of 95.3% 239.3% , 219.2% and 266.8% respectively compared to control.